Intermedial Studies An Introduction to Meaning Across Media - Bruhn, Jørgen; Schirrmacher, Beate (Taylor & Francis, 2022)
Intermedial Studies provides a concise, hands-on introduction to the analysis of a broad array of texts from a variety of media - including literature, film, music, performance, news and videogames, addressing fiction and non-fiction, mass media and social media. The detailed introduction offers a short history of the field and outlines the main theoretical approaches to the field. Part I explains the approach, examining and exemplifying the dimensions that construct every media product. The following sections offer practical examples and case studies using many examples, which will be familiar to students, from Sherlock Holmes and football, to news, vlogs and videogames. This book is the only textbook taking both a theoretical and practical approach to intermedial studies. The book will be of use to students from a variety of disciplines looking at any form of adaptation, from comparative literature to film adaptations, fan fictions and spoken performances. The book equips students with the language and understanding to confidently and competently apply their own intermedial analysis to any text.